A prospective observational study of ototoxicity in head and neck cancers treated with chemoradiotherapy - Feshan, Musarrat; Puthukudy, Preetham A.; Devadass, Brema (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Head and neck cancer is a major global health problem. Cisplatin has been widely used in the treatment of head and neck malignancies. Ototoxicity is considered as the primary outcome of interest and the type of hearing loss is the secondary variable of interest. The Chi-square test/Fisher’s exact test is used to test statistical significance. P value<0.05 is considered statistically significant. IBM statistical package for the social sciences (SPSS) version 22 is used for statistical analysis. Methods: In this prospective observational study, 62 patients with head and neck cancers were evaluated for chemoradiotherapy-induced ototoxicity. The hearing assessment included air and bone conduction thresholds, frequency, and pattern of hearing loss. The assessment was done at baseline, at the end of treatment, and after 8 weeks of completion of chemoradiotherapy. Results: Results showed the mean age group to be, between 61 to 70 years. Gender distribution showed that 80.65% are males and 19.35% are females. The most common site of malignancy is the larynx (20.97%). Cisplatin is used in 51 patients (82.26%) and carboplatin in 7 patients (11.29%). Radiotherapy was given to 82.26% of the patients. Results showed an increased incidence of sensorineural hearing loss (SNHL) after 8 weeks of treatment. There was a statistically significant difference between pure tone average (PTA) values before treatment, at the end of treatment, and after 8 weeks of chemoradiotherapy. Conclusions: Pure-tone hearing threshold was most affected at 8 kHz and sensorineural hearing loss at higher frequencies is the most common finding.